1984
DOI: 10.1016/0014-5793(84)80630-4
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct quinone‐modulated modes of antimycin‐sensitive cytochrome b reduction in the cytochrome bc1 complex

Abstract: Reduction of cytochrome b-560 (analogous to cyt b-562 of mitochondria) via an antimycin-sensitive route has been revealed in chromatophores of the photosynthetic bacterium, Rhodqpseudomonas sphaeroides Ga. Indeed, the results suggest that two reductive mechanisms can be operative. One is consistent with the idea that the quinol generated at the reaction center Q,site enters the Q pool and, via the Q,site, equilibrates with cytochrome b-560. The other reductive mode circumvents redox equilibrium with the pool; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…To estimate the affinity constant, Δ U H T of AGPS was calculated according to equation 6 [13] using ThermoFAD output, and Δ U C p was estimated according to AGPS size and structure [19]. The calculation of the estimated Kd was performed according to equation 14 [13], intentionally considering a range of uncertainty due to the reasonable assumption of Δ b H Tm being 40 kJ/mol (relatively unimportant for the overall Kd calculation).…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the affinity constant, Δ U H T of AGPS was calculated according to equation 6 [13] using ThermoFAD output, and Δ U C p was estimated according to AGPS size and structure [19]. The calculation of the estimated Kd was performed according to equation 14 [13], intentionally considering a range of uncertainty due to the reasonable assumption of Δ b H Tm being 40 kJ/mol (relatively unimportant for the overall Kd calculation).…”
Section: Methodsmentioning
confidence: 99%
“…(3) QH2 Oxidation at the Q¡ Site. At alkaline pH values and in the presence of the Q0 site inhibitor myxothiazol, it has been demonstrated that it is both thermodynamically and kinetically feasible for QH2 at the Q¡ site to reduce cyt bu Robertson et al, 1984a; Figure 7, event 3). The details of the reaction are unclear, but it appears to be either an equilibration of QH2 in the pool with cyt bu or a direct interaction of Qb with cyt bu-We took advantage of this pathway of electron transfer between QH2 at the Q¡ site and cyt bu to compare the rates and extents of cyt ¿>h reduction in the wild-type and mutant strains.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the heme b h could be reduced via center N by the RC-generated ubiquinol in the presence of myxothiazol at pH > 8.0. 90, 91 The reaction was accompanied by a blue carotenoid bandshift indicating a discharge of Dw; this shift was not observed in the presence of antimycin. 73,88 This negative electrogenesis was more pronounced in the presence of Dw.…”
Section: Electrogenic Reactions In Bcmentioning
confidence: 98%